Factors Related to Treatment Failure in Patients under Methadone Treatment at Drug Rehabilitation Centers - Ali Riahi; Narges Khanjani; Habibeh Ahmadipoor (Kerman University of Medical Sciences, 2015)
Introduction: One of the ways for addiction control and damage reductionis methadone treatment. However, the factors related to treatment failure have not been fully studied. In this study the characteristics related to treatment failure in Rafsanjan city has been studied. Method: This descriptive and analytical cross-sectional study was done based on records of patients visiting two rehabilitation centers in Rafsanjan in 2011-2013. The records were evaluated in two groups of patients. The first group (291 patients) were people with treatment failure, and the second group (309 people) were those successfully treated. Data analysis was done usingt-test, chi-square, and logistic regression through SPSS 22 software. Results: The mean age of participants was 37±10.5 years. The two groups were significantly different in regard to kind of substance use (P =0.001), existence of mental illness (P = 0.011), treatment center (P<0.001), the dose of methadone consumption (P= 0.018), and marital status (P< 0.001) but the difference in age, addiction duration, the concomitant use of two or more psychotropic substances, number of previous treatment, presence of physical illness, and the history of legal problems was insignificant. Conclusion: Methadone maintenance treatment is likely to be more effective if it is associated with treating the patients' mental illness, solving family problems, adequate doses of methadone, and reducing the health care costs. Keywords: Methadone, Maintenance therapy, Treatment failure, Rehabilitation Centers Citation: Riahi A, Khanjani N, Ahmadipour H. Factors Related to Treatment Failure in Patients under Methadone Treatment at Drug Rehabilitation Centers. Journal of Health Based Research 2015 1(2): 115-122.